A guide to the Personal Property Security Act: The case of Malawi - Marek Dubovec (Pretoria University Law Press (PULP), 2015)
About the publication This book examines the Malawian Personal Property Security Act (PPSA) of 2013 that is based on the United Nations Commission of International Trade Law's Legislative Guide on Secured Transactions. The PPSA is the first of its kind in Africa but there are several countries, including Ghana, Kenya, Liberia, South Sudan and Zambia that are in the process of undertaking similar reforms. One of the authors is directly involved as a consultant to the International Finance Corporation of the World Bank Group in all of these countries. Secured transactions have already become an important area of law introducing new concepts for the legal profession, lenders and borrowers in Africa. The book provides commentaries on individual sections of the PPSA that include practical examples, hypotheticals, illustrations of lending practices, relevant scholarly writings, and case law from the jurisdictions that inspired this reform, including Australia, Canada, New Zealand and the United States. This book seeks to provide an easy to read guide that is accessible to lawyers, judges and creditors who will use the law on a daily basis but also to foreign policymakers considering a similar reform. The IFC is about to launch a reform initiative of this kind in South Africa. This remarkable work offers a rare, broad and comprehensive examination of the law relating to secured transactions in Malawi. It comes at the right moment as it focuses on the newly enacted Personal Property Security Act. The authors have succeeded in covering an impressive number of intricate legal questions on the subject with great ease and clarity. The book brings together topics that frequently raise problems in this area of law but which are rarely analysed together and it enriches the perspectives of the reader with a lot of cross -jurisdictional references. It is a' must have' for lenders, borrowers and their respective legal advisors. It is also a useful eye opener on the subject for the discerning law student. Kalekeni Kaphale Attorney General, Lilongwe, Malawi Comments: Modernisation of law or law reform in the area of Personal Property Security Law has always been thought as a romantic and an abstract goal. The recent reform in Malawi in this field is a good example of how modernisation of law can be achieved. This book does an excellent job in picking out the principal issues in and challenges associated with the law reform in the area of Personal Property Security Law by an insightful and incisive analysis of the emerging policy questions in Malawian Law. Dr Orkun Akseli Durham University Law School, UK This book offers clear and concise commentary on the Malawian law of secured transactions - the Personal Property Security Act (PPSA). It explains the fundamental concepts underlying the PPSA, such as that of unitary and functional security interest, illustrates the application of its provisions in hypothetical situations, references similar laws in Australia, Canada, New Zealand and the United States and overall provides useful guidance to the users. It is unique in that it provides insights into the drafting of the PPSA itself in which both authors were actively involved. In view of the fact that the PPSA of Malawi implements to a large extent the recommendations of the UNCITRAL Legislative Guide on Secured Transactions, the authors included numerous references to the relevant recommendations of the Guide and its commentaries to direct the user to an invaluable source for further guidance and interpretation. So, this book is yet another testament of the growing influence of the UNCITRAL Legislative Guide on Secured Transactions on both the drafting of secured transactions legislation and its interpretation. This book will not only provide indispensable guidance to the users of the Malawian PPSA but could become an important tool in the implementation of similar reforms in the Sub-Saharan African countries that have already undertaken or contemplate PPSA-like reforms. Spyridon V Bazinas Senior Legal Officer International Trade Law Division, Office of Legal Affairs (UNCITRAL Secretariat) About the Editor: Marek Dubovec is Senior Research Attorney at the National Law Center for Inter-American Free Trade, Arizona, United States Cyprian Kambili is Legal Specialist at the Ministry of Industry and Trade, Lilongwe, Malawi Table of Contents Foreword Introduction Using the UNCITRAL Legislative Guide as a tool for a secured transactions reform in sub-Saharan Africa: The case of Malawi 1 Introduction 2 A critical review of the current laws on secured transactions in Malawi 2.1 The Bills of Sale Act 2.2 The Farmers' Stop-Orders Act 2.3 The Commercial Credits Act 2.4 The Hire-Purchase Act 2.5 The Companies Act 3 General problems with the legal regime for secured transactions in Malawi 4 Comparative search for legislative solutions to secured transactions in Malawi 5 Final remarks The key concepts, definitions, scope and interpretation 1 Security interest 2 Floating security 3 Definitions 4 Scope of the PPSA Creation of a security interest 1 Conditions for creation of a security interest 2 Description of collateral 2.1 Description of proceeds 2.2 Description of after-acquired property 3 Giving value 4 Rights in the collateral or power to encumber Perfection of a security interest 1 Registration 2 Possession 3 Control 4 Special provisions of the PPSA on perfection Priority of security interests 1 General priority rules 2 Priority of purchase money security interests 3 Priority in accessions and manufactured or commingled goods 4 Transfers of collateral and priority 5 Special priority rules Registration system 1 Establishment of, features and functions of the registry 2 Content of financing statements: Registration information 2.1 Identification of the debtor 2.2 Identification of the secured party 2.3 Description of the collateral 2.4 The maximum amount secured 2.5 Other data 3 Rejection of a financing statement 4 Time of effectiveness, authorisation for registration and its verification 5 Impact of errors on the effectiveness 6 Duration of registration 7 Amendment to and discharge of registration 8 Searches of the registry 9 Duty of the secured party to provide information Default and remedies 1 Application of Part VIII 2 Secured party's right to take possession after default 3 Disposal of collateral 4 Notice of sale 5 Legal effect of disposal 6 Proposal of secured party to retain collateral 7 Enforcement of security interests in accessions 8 Right to redeem collateral and reinstate security agreement 9 Statutory remedy Transitional matters and applicable laws 1 Applicable laws 2 Transition 2.1 Repealed acts 2.2 Preservation of pre-PPSA security interests Bibliography